Der grosse Verhau (1971) & Willi Tobler und der untergang der 6. Flotte (1972) - Kluge, Alexander (München : Edition Filmmuseum, 2007)
In the first century of the third millenium, a galactic civil war is raging between governments, industrial giants and space pirates. "The Big Mess" features space captain Douglas, the priate couple Sterr, a space admiral and countless other characters trying to eke out a living in the cosmos. In "Willi Tobler and the Decline of the 6th Fleet", Willi endeavors to survive in a world where nihilstic galactic battles rage by taking a job at the center of power. But it’s the wrong side that he takes in this civil war. ## 1. Der grosse Verhau / The Big Mess (90 min.), 1971 -- Triebwerk-Husten / Engine Cough (11 min.), 1996 -- Lernprozess mit tödlichem Ausgang / Learning Process with a Deadly Outcome (1 min.), 1998 -- ##2. Willi Tobler und der Untergang der 6. Flotte / Willi Tobler and the Decline of the 6th Fleet (78 min.), 1972 -- Der Tag ist nah / The Day is Nigh (15 min.), 1997-- Raumfahrt als inneres Erlebnis / Spaceflight as an Internal Experience (15 min.), 1999 -- Das gab’s nur einmal (1 min.), 2006.
Onderzoek KASK Professioneel (OFVP)
Duits gesproken, ondertitels in Engels, Frans, Russisch, Chinees en Spaans
film
Keywords: Kluge, Alexander